Le terroir, un concept pour l’action dans le développement des territoires - Philippe Prévost (Éditions en environnement VertigO, 2014)
Between business and social uses of the word terroir and the corresponding meanings, a variety of mental representations of the word creates the difficulty in mobilizing among researchers and trainers. The transdisciplinary analysis proposed in this paper aims to identify better understanding and to identify the potential of this concept for research, development and training. The concept of terroir has been characterized by a multi-referentiality: on the one hand an object representing a local and cultural productive system, on the other hand a project of a community whose goals are subjective. This multi-referentiality gives some potentiel for the concept about (i) mediation in development projects in rural areas, (ii) interdisciplinary training of agronomists.